Hypoxia hits APOL1 in the kidney - Grampp, Steffen; Krüger, René; Lauer, Victoria; Uebel, Sebastian; Knaup, Karl; Naas, Julia; Höffken, Verena; Weide, Thomas; Schiffer, Mario; Naas, Stephanie; Schödel, Johannes (Kidney International, 2023)
Individuals of African ancestry carrying two pathogenic variants of apolipoprotein 1 (APOL1) have a substantially increased risk for developing chronic kidney disease. The course of APOL1 nephropathy is extremely heterogeneous and shaped by systemic factors such as a response to interferon. However, additional environmental factors operating in this second-hit model have been less well defined. Here, we reveal that stabilization of hypoxia-inducible transcription factors (HIF) by hypoxia or HIF prolyl hydroxylase inhibitors activates transcription of APOL1 in podocytes and tubular cells. An active regulatory DNA-element upstream of APOL1 that interacted with HIF was identified. This enhancer was accessible preferentially in kidney cells. Importantly, upregulation of APOL1 by HIF was additive to the effects of interferon. Furthermore, HIF stimulated expression of APOL1 in tubular cells derived from the urine of an individual carrying a risk variant for kidney disease. Thus, hypoxic insults may serve as important modulators of APOL1 nephropathy.
CRIS-Team Scopus Importer:2023-05-26
Keywords: chronic kidney disease; hypoxia; podocyte; transcription regulation